Preference for Fractal-Scaling Properties Across Synthetic Noise Images and Artworks - Viengkham, Catherine; Spehar, Branka (Frontiers in Psychology, 2018)
A large number of studies support the notion that synthetic images within a certain intermediate fractal-scaling range possess an innate aesthetic value. Interestingly, the fractal-scaling properties that define this intermediate range have also been found to characterise a vast collection of representational, abstract and graphic art. While some have argued that these statistic properties only serve to maximise the visibility of the artworks' spatial structure, others argue they are intrinsically tied to the artworks' aesthetic appeal. In this study, we bring together these two threads of research and make a direct comparison between visual preference for certain fractal-scaling characteristics in both synthetic images and artworks. Across two studies, viewers ranked and rated sets of fractal noise images and artworks that systematically varied in fractal dimension for liking, pleasantness, complexity and interestingness. We analysed both average and individual patterns of preference between the two image classes. Average preference peaked for intermediate fractal dimension values for both categories, but individual patterns of preferences for both high and low values also emerged. Correlational analyses indicated individual preferences between the two image classes remained moderately consistent and were improved when the fractal dimension between synthetic images and artworks were more closely matched. Overall, these findings further support the role of fractal-scaling statistics as both a key determinant of an object’s aesthetic value and as a valuable predictor of individual differences in aesthetic preference.